PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN DIVIDEN, PROFITABILITAS, KEBIJAKAN HUTANG DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN SEKTOR KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - kristanto, celine; Putri, Arie Pratania; Melisa, Melisa; Suriyani, Suriyani (2020)
This research was conducted to test and analyze whether there is an effect of managerial ownership, dividend policy, profitability, debt policy and investment decisions on firm value. This study used secondary data from financial statements downloaded from the website www.idx.co.id, with a population of 16 companies where only 9 samples met the criteria using a purposive technique so that the data that can be processed amounts to 36 data. The research data was tested using multiple regression and hypothesis partially and simultaneously. The results of this study are managerial ownership, dividend policy and debt policy do not have an effect on firm value while profitability and investment decisions have a positive effect on firm value. Managerial ownership, dividend policy, profitability, debt policy and investment decisions together affect the company's value in the construction sector with the 2014-2017 research period.